Zoominar: Peningkatan Pengetahuan Ibu Hamil tentang Pentingnya Kunjungan Antenatal Care: Zoominar: Increasing Knowledge of Pregnant Women about the Importance of Antenatal Care Visits - Ningsih, Fitriani; Putri, Elma Monica; Marlita, Marlita; Mantovani, Muhamad Rizal; Iman, Tia Feronika A.H. (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Antenatal care is a pregnancy examination to optimize the mental and physical health of pregnant women to deal with childbirth, the postpartum period, preparation for breastfeeding, and the return of reproductive health naturally. Antenatal care services by several pregnant women are still not entirely appropriately utilized; this makes it difficult for health workers to carry out regular and comprehensive health care development for pregnant women, including early detection of pregnancy risk factors. The purpose of this activity was carried out to increase the knowledge of pregnant women about antenatal care visits. The method used in this activity is lectures and questions and answers via Zoominar. The results of this activity were attended by 20 pregnant women; during the activity, the mothers were very enthusiastic; this could be seen in the increase in the mother’s knowledge before and after being given information.